Anatomical Variations of Horseshoe Kidney and their Effects on Kidney Stones and Renal Function - Irshad Khan, Sami Ul Haq, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Horseshoe kidneys (HSK) are a congenital anatomical variation in which the kidneys fuse at their lower poles, potentially leading to renal dysfunction and kidney stone formation. The impact of these anatomical changes on kidney stone development and renal function is poorly understood. This study investigates how anatomical variations in HSK affect kidney stone formation, renal function, and long-term kidney health outcomes. Objective: The primary objective of this study is to assess the relationship between horseshoe kidney anatomical variations and the formation of kidney stones, along with their effect on renal function. The study aims to compare the clinical, radiological, and functional outcomes of patients with horseshoe kidneys, both with and without kidney stones, against those with normal kidneys and kidney stones. Methods: A retrospective cohort study was conducted at the Institute of Kidney Diseases (IKD), Peshawar, from 2015 to 2018. A total of 300 patients were included and categorized into three groups: 100 patients with horseshoe kidneys and kidney stones (HSK+KS), 80 patients with horseshoe kidneys but no stones (HSK-KS), and 120 patients with normal kidneys and kidney stones (Normal+KS). Data collection included clinical symptoms, renal function tests (serum creatinine and GFR), and imaging findings (e.g., stone size, hydronephrosis, renal parenchymal thickness). Statistical analyses, including one-way ANOVA and chi-square tests, were performed to compare outcomes across groups. Results: Patients with HSK and kidney stones (HSK+KS) showed significantly worse renal function compared to the other groups, with a mean GFR of 70 ml/min and elevated serum creatinine levels (1.2 mg/dl). These patients also had larger stones (mean size of 7.5 mm) and higher rates of recurrent stones (30%). The prevalence of hydronephrosis was 25%, and 15% of these patients experienced CKD progression over the study period. In contrast, HSK patients without stones (HSK-KS) had a higher average GFR (90 ml/min), lower serum creatinine (0.9 mg/dl), and minimal hydronephrosis (10%). Conclusion: This study highlights the significant impact of horseshoe kidney anatomy on kidney stone formation and renal function. Patients with horseshoe kidneys and kidney stones experience more severe renal dysfunction and a higher risk of complications, including CKD progression, compared to those with normal kidneys. Early detection and targeted interventions are crucial to managing kidney stones and preserving renal function in these patients. Keywords: Horseshoe kidney, kidney stones, renal function, glomerular filtration rate (GFR), chronic kidney disease (CKD), hydronephrosis.